Commentary of the SKLM to the EFSA opinion on risk assessment of N-nitrosamines in food - Eisenbrand, Gerhard; Büttner, Andrea; Diel, Patrick; Epe, Bernd; Först, Petra; Grune, Tillman; Haller, Dirk; Heinz, Volker; Hellwig, Michael; Humpf, Hans Ulrich; Jäger, Henry; Kulling, Sabine; et al. (Archives of Toxicology, 2024)
Dietary exposure to N-nitrosamines has recently been assessed by the European Food Safety Authority (EFSA) to result in margins of exposure that are conceived to indicate concern with respect to human health risk. However, evidence from more than half a century of international research shows that N-nitroso compounds (NOC) can also be formed endogenously. In this commentary of the Senate Commission on Food Safety (SKLM) of the German Research Foundation (DFG), the complex metabolic and physiological biokinetics network of nitrate, nitrite and reactive nitrogen species is discussed with emphasis on its influence on endogenous NOC formation. Pioneering approaches to monitor endogenous NOC have been based on steady-state levels of N-nitrosodimethylamine (NDMA) in human blood and on DNA adduct levels in blood cells. Further NOC have not been considered yet to a comparable extent, although their generation from endogenous or exogenous precursors is to be expected. The evidence available to date indicates that endogenous NDMA exposure could exceed dietary exposure by about 2–3 orders of magnitude. These findings require consolidation by refined toxicokinetics and DNA adduct monitoring data to achieve a credible and comprehensive human health risk assessment.
CRIS-Team Scopus Importer:2024-04-12